10.5k views
3 votes
Given that f(x)=2x+1 and g(x)=3x-1/2 find g(f(3))

1. 5
2. 7
3. 9
4. 10

User Fomalhaut
by
6.2k points

2 Answers

5 votes

Answer:

10

Explanation:

You must substitute the 3 for the x in f(x) = 2x+1 first

f(x) = 7

Then substitute the 7 for the x in g(x) = (3x - 1)/2

g(x) = 10

User Sheldon Rong
by
5.9k points
3 votes

Answer:

7

Explanation:

Solve for the first variable in one of the equations, then substitute the result into the other equation.

User Vpozdyayev
by
6.6k points